Characterization of Klebsiella isolates by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) and determination of antimicrobial resistance with VITEK 2 advanced expert system (AES) - Karagöz, Alper; Acar, Sümeyra; Körkoca, Hanifi (My University, 2015)
Background/aim: The purpose of the study was to evaluate the performance of the VITEK mass spectrometry (MS) (bioMérieux, France) system for the identification of Klebsiella spp. isolated from different sources. Moreover, while assessing the ability of the VITEK 2 automated expert system (AES) to recognize antimicrobial resistance patterns, the researchers have extended the study to compare VITEK 2 with the routine antimicrobial susceptibility testing method. Materials and methods: This study tested 51 Klebsiella spp. isolates that were isolated from environmental examples and clinical examples. Results of conventional methods and the matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) MS were compared. Then, any differing results were compared against a reference 16S rRNA gene sequence, and when indicated, a recA sequencing analysis was done. Results: VITEK MS correctly identified 100% of the Klebsiella spp. isolates. There were two K. oxy toca isolates incorrectly identified to the species level with conventional methods according to the 16S rRNA gene sequencing analysis. In addition, a VITEK 2 AST-N261 card was used for the detection of extended spectrum beta-lactamases (ESBL). Using the VITEK 2 AES, ESBL positivity was found at the rate of 16.3% whereas this rate was 4.08% using the disk diffusion method. Conclusion: MALDI-TOF MS is a rapid and accurate method for the identification of Klebsiella spp. Moreover, the bioMérieux AES provides a useful laboratory tool for the interpretation of susceptibility results.
Keywords: Cerrahi